2007
DOI: 10.1002/adma.200700021
|View full text |Cite
|
Sign up to set email alerts
|

Monoclinic Ferroelastic Domains in LaCoO3‐Based Perovskites

Abstract: LaCoO 3 -materials have received considerable attention due to their novel magnetic properties [1][2][3] and mixed ionicelectronic conductivity at elevated temperatures leading to exciting applications such as electrodes in solid oxide fuel cells [4] and oxygen permeable membranes.[5] Perovskites such as LaCoO 3 and related materials like LaAlO 3 undergo a displacive phase transition from a paraelastic cubic perovskite with space group Pm 3m at high temperatures to a ferroelastic rhombohedral perovskite with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 38 publications
1
47
0
Order By: Relevance
“…[15,29,30] Thermal conductivity and electrical resistivity also undergo interest- ing changes in the 10K < T < 300K region. [31,25,32,33] Possible sources of magnetic moment are the twinning interfaces that appear in the bulk LCO [34,5,35] and possibly in nanoparticles. Putting strain on thin LCO films can create such interfaces near the substrate interface.…”
mentioning
confidence: 99%
“…[15,29,30] Thermal conductivity and electrical resistivity also undergo interest- ing changes in the 10K < T < 300K region. [31,25,32,33] Possible sources of magnetic moment are the twinning interfaces that appear in the bulk LCO [34,5,35] and possibly in nanoparticles. Putting strain on thin LCO films can create such interfaces near the substrate interface.…”
mentioning
confidence: 99%
“…Thanks to the advancements in imaging techniques over the past several decades, the structural components contributing to these interfacial phenomena can be identified and used in the interpretation of new nanoscale behavior. [25][26][27][28] In this work, we probe the microstructure of epitaxial SCO films grown on STO substrates using scanning transmission electron microscopy (STEM), which can reveal the influence of symmetry mismatch-driven strain upon the interfacial architecture. Using geometric phase analysis [29,30] (GPA), we carefully mapped out the strain-variation existing between two different domain structures.…”
mentioning
confidence: 99%
“…From these results, it is suggested that the rhombohedral LSCF is not ideally elastic and the decrease in the elastic modulus of LSCF is related with nonelastic effects. Furthermore, the rhombohedral LSCF is known to show ferroelastic behavior [9][10][11] . The rhombohedral crystal structure of LSCF is formed by the compression of the ideal cubic structure along the <111> directions of a cubic unit cell.…”
Section: Introductionmentioning
confidence: 99%